Improving Teacher Ability in Preparing Daily Test Assessment Questions Through Workshops - Lahay, Muhammad Yunan (Pinisi Journal of Education and Management, 2022)
The problem in this study is the low ability of teachers in compiling daily test assessment questions at SMAN 1 Lamala. The purpose of the research is to improve the teacher's ability in preparing daily test assessment questions through the implementation of workshop activities. The research subjects were 12 teachers at SMAN 1 Lamala. Data collection techniques with observation and documentation techniques. Data analysis was carried out using a comparative descriptive technique. The results of the observation assessment of discussion activities showed that the initial bad criteria increased to the sufficient criteria in the first cycle At the end of the second cycle. An explanation of improving the ability of teachers in Compiling Daily Test Assessment Questions in the initial conditions of bad qualifications, and in the first cycle the results showed in qualification C or sufficient and at the end of the second cycle increased in very good qualifications. In terms of increasing the ability of teachers in preparing individual daily test questions, it shows an increase.